Inhibiting the endoplasmic reticulum stress response enhances the effect of doxorubicin by altering the lipid metabolism of liver cancer cells - Maria Kopsida; Ada Lerma Clavero; Jaafar Khaled; David Balgoma; Clara Luna-Marco; Azazul Chowdhury; Sofi Sennefelt Nyman; Fredrik Rorsman; Charlotte Ebeling Barbier; Peter Bergsten; Hans Lennernäs; Mikael Hedeland; et al. (Elsevier, 2024)
Hepatocellular carcinoma (HCC) is characterized by a low and variable response to chemotherapeutic treatments. One contributing factor to the overall pharmacodynamics is the activation of endoplasmic reticulum (ER) stress pathways. This is a cellular stress mechanism that becomes activated when the cell's need for protein synthesis surpasses the ER's capacity to maintain accurate protein folding, and has been implicated in creating drug-resistance in several solid tumors. Objective: To identify the role of ER-stress and lipid metabolism in mediating drug response in HCC. Methods: By using a chemically-induced mouse model for HCC, we administered the ER-stress inhibitor 4μ8C and/or doxorubicin (DOX) twice weekly for three weeks post-tumor initiation. Histological analyses were performed alongside comprehensive molecular biology and lipidomics assessments of isolated liver samples. In vitro models, including HCC cells, spheroids, and patient-derived liver organoids were subjected to 4μ8C and/or DOX, enabling us to assess their synergistic effects on cellular viability, lipid metabolism, and oxygen consumption rate. Results: We reveal a pivotal synergy between ER-stress modulation and drug response in HCC. The inhibition of ER-stress using 4μ8C not only enhances the cytotoxic effect of DOX, but also significantly reduces cellular lipid metabolism. This intricate interplay culminates in the deprivation of energy reserves essential for the sustenance of tumor cells. Conclusions: This study elucidates the interplay between lipid metabolism and ER-stress modulation in enhancing doxorubicin efficacy in HCC. This novel approach not only deepens our understanding of the disease, but also uncovers a promising avenue for therapeutic innovation. The long-term impact of our study could open the possibility of ER-stress inhibitors and/or lipase inhibitors as adjuvant treatments for HCC-patients.